Enhancing Schools’ Capacity to Support Children in Poverty: An Ecological Model of School-Based Mental Health Services - Cappella, Elise (2008)
School based mental health services for children in poverty can capitalize on schools’ inherent capacity to support development and bridge home and neighborhood ecologies. We propose an ecological model informed by public health and organizational theories to refocus school based services in poor communities on the core function of schools to promote learning. We describe how coalescing mental health resources around school goals includes a focus on universal programming, mobilizing indigenous school and community resources, and supporting core teaching technologies. We suggest an iterative research–practice approach to program adaptation and implementation as a means toward advancing science and developing healthy children.